Effect of nb and zn element doping on barium strontium cobalt ferrite-based cathode for solid oxide fuel cell – a short review - Yusop, Umira Asyikin; Abd Rahman, Nurul Farhana; Anak Lowrance, Yohannes Nyambong; Jaidi, Zolhafizi; Tukimon, Mohd Faizal; Azmi, Mohd Azham; Ismail, Azzura; Mahzan, Shahruddin; Abd Rahman, Hamimah (Microscopy Society of Malaysia (MSM), 2022)
Alternative energy sources are needed to meet global energy demands, and a dependable solid oxide fuel cell (SOFC) has demonstrated system reliability. The commercialization of SOFC, especially for intermediate to low-temperature applications, can be widely achieved after meeting a few system requirements and locating suitable material candidates. Therefore, this review is conducted to observe the current approach to the material development for intermediate temperature SOFC (IT-SOFC) and the influence of doping the element on BSCF-based cathode properties. This article reviewed two types of doping elements, namely, Niobium (Nb) and Zinc (Zn), and their chemical, physical, thermal and electrochemical characteristics. The dopant material was substituted in the B-site of BSCF cathode material to increase the cell performance. As observed from the study, it greatly enhanced the performance and chemical stability of BSCF as a cathode material. Interestingly, Nb-doping increased the chemical stability and CO2 tolerance of BSCF-based materials under high oxidation conditions, while Zn doping improved the electrocatalytic activity of the oxygen reduction (ORR) process. This review found that BSCF perovskite is an attractive and promising candidate material for SOFC. Still, the compatibility of the cathode material in terms of chemical, physical, thermal and electrochemical properties should be further investigated to achieve optimum parameters for outstanding cell performance.